(untitled) (Purbanchal University Health Journal, 2022)
Adenomatoid odontogenic tumor (AOT), which appears mostly in young females with highest occurrence in the maxillary region, is a hamartomous benign neoplasm of odontogenic origin. It is a slow growing, asymptomatic lesion but hampering the esthetics. It is mainly related to non-erupted canines. Lesions of this type can be classified as follicular, extra follicular and peripheral lesions. Treatment of these lesions is enucleation and curettage of the affected area. Recurrence is rare. A case of adenomatoid odontogenic tumor in a twelve year old female which was associated with an impacted maxillary left canine teeth has been reported in this paper.